THE USE OF CONTENT-BASED INSTRUCTION IN TEACHING READING FOR SECOND GRADE OF SENIOR HIGH SCHOOL - Azizatul Wafiroh; Sukma Nur Ardini; Fitri Yulianti (English Language Education Department, Universitas Majalengka, 2022)
The aims of this study were to find out the effectiveness of Content-Based Instruction method in teaching reading for second grade of SMAN 1 Donorojo Jepara and to find out the reading comprehension ability of the second grade of SMAN 1 Donorojo Jepara. The population of this study was from the second grade MIPA which consists of 143 students from 4 classes. The samples of this study were class XI MIPA 2 as control group and class XI MIPA 4 as experimental group. The samples were selected by random sampling technique. The instruments used in this study were reading pre-test and post-test. The data were collected from observation and reading comprehension tests. The data were analyzed statistically in the form of t-test. To find out the significant improvement, the researchers conducted t-test using Paired Sample t-test, it showed that the sig. (2-tailed) of experiment is 0.00 and control group is 0.02. 0.000 < 0.05 and 0.02 < 0.05. There is a significance difference in the result of students' learning scores between the experiment and control group. The students' ability in reading comprehension in second grade of senior high school in SMA Negeri 1 Donorojo Jepara in comprehending English text is poor, after taught using CBI method, the frequency of post-test increased from poor to very good.Teachers may use the CBI method as an effective and innovative teaching method to improve students' reading skill. CBI method is also recommended to be applied in the hybrid classrooms.